Current developments and future perspectives of nanotechnology in orthopedic implants: an updated review - Liang, Wenqing; Zhou, Chao; Bai, Juqin; Zhang, Hongwei; Long, Hengguo; Jiang, Bo; Dai, Haidong; Wang, Jiangwei; Zhang, Hengjian; Zhao, Jiayi (Frontiers in Bioengineering and Biotechnology, 2024)
Orthopedic implants are the most commonly used fracture fixation devices for facilitating the growth and development of incipient bone and treating bone diseases and defects. However, most orthopedic implants suffer from various drawbacks and complications, including bacterial adhesion, poor cell proliferation, and limited resistance to corrosion. One of the major drawbacks of currently available orthopedic implants is their inadequate osseointegration at the tissueimplant interface. This leads to loosening as a result of immunological rejection, wear debris formation, low mechanical fixation, and implant-related infections. Nanotechnology holds the promise to offer a wide range of innovative technologies for use in translational orthopedic research. Nanomaterials have great potential for use in orthopedic applications due to their exceptional tribological qualities, high resistance to wear and tear, ability to maintain drug release, capacity for osseointegration, and capability to regenerate tissue. Furthermore, nanostructured materials possess the ability to mimic the features and hierarchical structure of native bones. They facilitate cell proliferation, decrease the rate of infection, and prevent biofilm formation, among other diverse functions. The emergence of nanostructured polymers, metals, ceramics, and carbon materials has enabled novel approaches in orthopaedic research. This review provides a concise overview of nanotechnology-based biomaterials utilized in orthopedics, encompassing metallic and nonmetallic nanomaterials. A further overview is provided regarding the biomedical applications of nanotechnology-based biomaterials, including their application in orthopedics for drug delivery systems and bone tissue engineering to facilitate scaffold preparation, surface modification of implantable materials to improve their osteointegration properties, and treatment of musculoskeletal infections. Hence, this review article offers a contemporary overview of the current applications of nanotechnology in orthopedic implants and bone tissue engineering, as well as its prospective future applications.